2011
DOI: 10.1111/j.1945-1474.2010.00121.x
|View full text |Cite
|
Sign up to set email alerts
|

Putting a Face on Medical Errors: A Patient Perspective

Abstract: Knowledge of the patient's perspective on medical error is limited. Research efforts have centered on how best to disclose error and how patients desire to have medical error disclosed. On the basis of a qualitative descriptive component of a mixed method study, a purposive sample of 30 community members told their stories of medical error. Their experiences focused on lack of communication, missed communication, or provider's poor interpersonal style of communication, greatly contrasting with the formal defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…9 A 2015 literature review showed disclosure to be a significant topic of debate. 8 The few primary research studies of patient experiences of open disclosure processes 9,[11][12][13][14] have consistently found that open disclosure did not meet patient expectations. In Australia, the 100 Patient Stories project found that although patients welcomed open disclosure, they were not adequately followed-up with tangible support or information about changes in practice, were not being offered an apology and were not being given the opportunity to meet with staff directly involved in the event.…”
Section: Introductionmentioning
confidence: 99%
“…9 A 2015 literature review showed disclosure to be a significant topic of debate. 8 The few primary research studies of patient experiences of open disclosure processes 9,[11][12][13][14] have consistently found that open disclosure did not meet patient expectations. In Australia, the 100 Patient Stories project found that although patients welcomed open disclosure, they were not adequately followed-up with tangible support or information about changes in practice, were not being offered an apology and were not being given the opportunity to meet with staff directly involved in the event.…”
Section: Introductionmentioning
confidence: 99%
“…One study which explored how patients had experienced disclosure and error described patients reporting that the actual error was less concerning than the continued relationship with their health-care provider. 84 These individuals described being treated not as experts in their own experience of care, but as outsiders. The authors described this as patients feeling like a foreigner in a strange land experiencing a different culture and language, and highlight how poor communication suggests a conflict between a model of person-centred care, with the patient-provider relationship at its heart, and the business or corporate model of health care.…”
Section: Recognising Patient and Caregiver Expectationsmentioning
confidence: 99%
“…A number of individuals highlight the role that patients and families may have. 84 Patients and their families often have a unique perspective on their experiences and can provide information and insights that health-care providers and systems administrators may not appreciate or know. 108 Allowing patients and families to engage in a dialogue as part of disclosure allows them to describe what may be important insights into factors leading up to and following health-care incidents, and emotional harms that occur when these incidents are inadequately communicated or responded to, and to make a potential contribution to patient safety.…”
Section: Learning From Mistakes and Errormentioning
confidence: 99%
“…Ensuring quality health care and positive health outcomes for patients is a priority for health care providers (ANA, 2001(ANA, , 2010CNA, 2008;CNO, 2002). However, researchers suggest that definitions and measurements of quality health care developed from the perspective of patients are lacking (Brown, 2007;Kooienga & Stewart, 2011;Wong, Watson, Young, & Regan, 2008). A qualitative thematic content analysis of telephone interviews with 30 patients was conducted as part of a larger randomized, experimental design, mixed methods study to explore patients' perspectives on quality health care and the meaning of health care error (Kooienga & Stewart, 2011).…”
Section: Qowl Predictors and Patient Outcomesmentioning
confidence: 99%
“…However, researchers suggest that definitions and measurements of quality health care developed from the perspective of patients are lacking (Brown, 2007;Kooienga & Stewart, 2011;Wong, Watson, Young, & Regan, 2008). A qualitative thematic content analysis of telephone interviews with 30 patients was conducted as part of a larger randomized, experimental design, mixed methods study to explore patients' perspectives on quality health care and the meaning of health care error (Kooienga & Stewart, 2011). Patients reported that health care errors were associated with lack of communication and poor communication skills among health care providers (Kooienga & Stewart, 2011).…”
Section: Qowl Predictors and Patient Outcomesmentioning
confidence: 99%